Gelis Sambul Service as Moderating Effect of Tax Collection System and Fiscal Services on Taxpayer Compliance - Wiguna, I Gede Nandra Hary; Dewi, Ayu Wulan Trisna; Julianto, I Putu (Universitas Pendidikan Ganesha, 2023)
This study examines the effect of the tax collection system and tax services on taxpayer compliance with the gelis sambul service as a moderator. The research was conducted on the taxpayers of the Joint Samsat Office of Buleleng Regency. The number of samples as many as 99 people using the slovin technique. Methods of data collection using a questionnaire with multiple linear regression data analysis techniques and Moderated Regression Analysis (MRA). The results of hypothesis testing indicate that the tax collection system and service tax authorities have a positive effect on taxpayer compliance. The gelis sambul service variable is also able to moderate the effect between the tax collection system and taxpayer compliance. Meanwhile, the effect of the tax service on taxpayer compliance was not moderated by the gelis sambul service